Edukasi penyakit malaria dan pengobatan menggunakan obat herbal pasca gempa di Lombok - Windah Anugrah Subaidah; Yohanes Juliantoni; Wahida Hajrin (Universitas Mataram, 2021)
In September 2018 malaria was identified as an extraordinary event in NTB. Malaria plague spread in West Lombok. According to data from the West Lombok health service there were 184 cases. This includes pregnant women, children, and babies. Severe impact on vulnerable groups such as pregnant women and children. Pregnant women infected with malaria will experience severe anemia and have a higher risk of fetal death. In children, it affects the growth and intelligence disorders caused by anemia. The purpose of this community service was to increase the knowledge about malaria disease and ways to prevent it. The method is done by presenting the method, then followed by an interactive discussion and giving evaluation through post-test and pre-test. The service was carried out at the Senggigi village office in Batu Layar District, West Lombok Regency, West Nusa Tenggara Province. The contents of the presentation were what is malaria, how to prevent malaria, and how to use herbal medicine to cure malaria. Afterward, the committee distributed leaflets and abate powders to participants. The evaluation showed there was an increase in the knowledge of participants after education was given. The increase of knowledge about malaria would decrease the number of malaria cases at Senggigi village